Pengembangan E-Book Berbasis Creative Problem Solving Terintegrasi STEM pada Materi Perubahan Lingkungan untuk Siswa SMA - Izza Melati Sukma; Aditya Marianti; Ellianawati (Jurnal Penelitian Pendidikan IPA, 2023)
Critical and creative thinking skills are very important in the 21st century. The creative problem-solving learning model and the STEM approach are suitable for training critical and creative thinking skills in learning. This study aims to: 1) analyze the need for an e-book based on creative problem solving integrated with STEM, hereinafter referred to as BOTIPOSTEM and 2) analyze the eligibility of BOTIPOSTEM. This type of research is research and development (R&D) using the ADDIE model. Research data were obtained through interviews, questionnaires, validation sheets, and readability sheets. The data were analyzed descriptively quantitatively and using Aiken's V. The results showed that: 1) the development of BOTIPOSTEM is in the very needed category based on the teacher's response; 2) BOTIPOSTEM obtained an average Aiken score of 0.96 by material experts and 0.92 by media experts, the percentage of readability obtained an average score of 96% by teachers and 93% by students. Data analysis shows that BOTIPOSTEM has a high level of validity and readability. Thus it can be concluded that BOTIPOSTEM is very much needed and eligible to used in learning to train students' critical and creative thinking skills at school.